The Effect of Artificial Intelligence (AI), Capital Adequacy Ratio (CAR), and Non-Performing Loan (NPL), on Return on Assets (ROA) of Banking Companies Limited on the Indonesia Stock Exchange (Idx) - Ramadhany, Adytia Putra; Perkasa, Didin Hikmah (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the effect of Artificial Intelligence (AI), the Capital Adequacy Ratio (CAR), and Non-Performing Loans (NPL) on Return on Assets (ROA) in banking companies listed on the Indonesia Stock Exchange (IDX). This research employed a quantitative approach using secondary data obtained from the financial statements of banks that experienced losses during the 2022–2025 period. The sample was selected using a purposive sampling technique based on predetermined criteria, resulting in 20 observation samples. The data were analyzed using IBM SPSS through descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The results show that Artificial Intelligence (AI) has a positive and significant effect on Return on Assets (ROA). The Capital Adequacy Ratio (CAR) has a positive but insignificant effect on Return on Assets (ROA). Meanwhile, Non-Performing Loans (NPL) have a negative and significant effect on Return on Assets (ROA). These findings indicate that the implementation of Artificial Intelligence (AI) can improve banking profitability, while a high level of non-performing loans reduces profitability. Therefore, banks are expected to implement Artificial Intelligence (AI) in their operational activities, particularly in credit analysis, to reduce the level of non-performing loans and improve financial performance.